MAGMATIC ARC EVOLUTION IN THE PONGKOR EPITHERMAL GOLD MINERALISATION DISTRICT - Anastasia Dewi Titisari, Anastasia Dewi Titisari (Jurusan Teknik Geologi, 2014)
The Pongkor epithermal gold mineralisation district is located approximately 80 km southwest of Jakarta. This district hosts the largest gold vein deposits in Java, Indonesia. Although the Pongkor district has been the subject of several geological studies, the arc evolution in relation to gold mineralisation is less well understood. The timing and geochemical evolution of the Pongkor volcanic rocks provide an important background to understanding the volcanic successions of this magmatic arc in relation to epithermal gold mineralisation. This study presents 40 Ar/ 39 Ar age results, and major and trace element data for the Pongkor volcanic rocks associated with epithermal gold deposition in the region. A sequence of volcanic rocks of basaltic – dacitic composition, consisting of volcanic breccias, lapilli tuffs and andesites, form the host volcanic rocks to the Pongkor epithermal gold mineralisation. 40 Ar/ 39 Ar dating of the andesitic samples yielded an average age of 2.74 ± 0.03 Ma. However, petrographic studies and the younger ages of 2.48 ± 0.01 Ma and 2.09 ± 0.04 Ma obtained from andesitic and basaltic andesite samples, respectively,imply that these samples were affected by alteration; therefore the ages probably relate more to the time of hydrothermal alteration than volcanic eruptions. Enriched LILE (Large Ion Lithopile Element) and LREE (Light Rare Earth Element) compositions for basalt – andesite samples from the Pongkor district are characteristic of calc-alkaline arcs. On the other hand, some andesite samples are characterized by more enriched LILE and LREE compositions, which are indicative of high-K calc-alkaline and shoshonite arcs. Trends in Nb/Y, Th/Nb, and Ce/Yb, ratios of the volcanic samples reflect temporal evolution of the arcs, from a mature arc (intermediate Nb/Y, Th/Nb and Ce/Yb ratios) representedby the calc-alkaline volcanic samples, to an evolved arc (high Nb/Y, Th/Nb and Ce/Yb values) typified by the high-K calc-alkaline – shoshonite volcanic samples. Keyword: 40 Ar/ 39 Ar dating, Magmatic arc evolution, Pongkor District, Volcanism